Micromechanical testing of ultrathin layered material specimens at elevated temperature. (28th June 2016) - Texier, D.; Monceau, D.; Salabura, J. C.; Mainguy, R.; Andrieu, E.
Abstract: The mechanical characterisation of ultrathin specimens at very high temperature is challenging in terms of specimen preparation and mechanical testing under 'inert' atmospheres. An experimental procedure for the local characterisation of mechanical and thermal properties at elevated temperature is presented. Various common 'inert' atmospheres were investigated up to 1373 K in order to identify the most efficient environmental conditions to prevent surface reactivity and degradation of specimens. A NiCoCrAlYTa-coated monocrystalline Ni-based superalloy was used to exemplify the capabilities of the technique because of its high surface reactivity at very high temperature, i.e. oxidation and sublimation. Purified overpressured argon atmosphere combined with oxygen getters was found to be particularly suitable for the study of alumina-forming alloys at elevated temperature.